The translation of negative politenes in garcía márquez’s novel cien años de soledad (2014)
This paper presents an empirical contrastive corpus-based analysis of the translation of negative politeness from Spanish into English of the direct verbal interactions in Garcia Marquez’s novel Cien años de soledad, which are strongly determined by their cultural, social and situational context. This study assesses, both qualitatively and quantitatively, the extent to which these strategies are maintained, adapted or eliminated in the conversational interactions translated from a positive politeness-oriented culture (Colombia) into a negative politeness-oriented culture (English language readers). It could be concluded that in the translation, the pragmatic meaning of the speech acts involved was maintained for the most part, by rendering into the TT a similar type and amount of negative politeness strategies and substrategies.